Twenty years of Kura-Araxes research at Tel Bet Yerah: What we have learned - Greenberg, Raphael; Iserlis, Mark; Paz, Sarit (ARAMAZD: Armenian Journal of Near Eastern Studies, 2022)
Tel Bet Yerah has provided us with an opportunity to advance the study of diasporic Kura-Araxes research in multiple ways. Reflecting on what we have learned in twenty years at the site, we summarize the evidence for an assemblage that goes far beyond Khirbet Kerak ceramics, and includes the organization of space, miniature art, stone and metal artifacts, food and fuel acquisition and consumption practices. We also reflect on our evolving understanding of migration and interaction with local cultures and on the role of intentionality in maintaining cultural and political distinction.